Sonic Hedgehog Signaling Drives Proliferation of Synoviocytes in Rheumatoid Arthritis: A Possible Novel Therapeutic Target. (6th March 2014) - Wang, Mingxia; Zhu, Shangling; Peng, Weixiang; Li, Qiuxia; Li, Zhaoxia; Luo, Minqi; Feng, Xiaoxue; Lin, Zhuofeng; Huang, Jianlin
Abstract : Sonic hedgehog (Shh) signaling controls many aspects of human development, regulates cell growth and differentiation in adult tissues, and is activated in a number of malignancies. Rheumatoid arthritis (RA) is characterized by chronic synovitis and pannus formation associated with activation of fibroblast-like synoviocytes (FLS). We investigated whether Shh signaling plays a role in the proliferation of FLS in RA. Expression of Shh signaling related components (Shh, Ptch1, Smo, and Gli1) in RA synovial tissues was examined by immunohistochemistry (IHC) and in FLS by IHC, immunofluorescence (IF), quantitative RT-PCR, and western blotting. Expression of Shh, Smo, and Gli1 in RA synovial tissue was higher than that in control tissue (P < 0.05 ). Cyclopamine (a specific inhibitor of Shh signaling) decreased mRNA expression of Shh, Ptch1, Smo, and Gli1 in cultured RA FLS, Shh, and Smo protein expression, and significantly decreased FLS proliferation. Flow cytometry analysis suggested that cyclopamine treatment resulted in cell cycle arrest of FLS in G1 phase. Our data show that Shh signaling is activated in synovium of RA patients in vivo and in cultured FLS form RA patients in vitro, suggesting a role in the proliferation of FLS in RA. It may therefore be a novel therapeutic target in RA.